2023
DOI: 10.1029/2023jd039459
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐Containing Functional Groups Dominate the Molecular Absorption of Water‐Soluble Humic‐Like Substances in Air From Nanjing, China Revealed by the Machine Learning Combined FT‐ICR‐MS Technique

Yihang Hong,
Yan‐Lin Zhang,
Mengying Bao
et al.

Abstract: The light absorption capacity of water‐soluble humic‐like substances (HULISWS) at the molecular level is crucial for reducing the uncertainties in modeling the radiative forcing. This study proposed a machine learning approach to allocate the light absorption coefficient at 365 nm (Abs365) of HULISWS into 8084 Fourier transform‐ion cyclotron resonance mass spectrometry (FT‐ICR‐MS) detached molecular markers and their potential functional groups. The ML model showed an acceptable uncertainty (<5%) to the who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 120 publications
(146 reference statements)
0
0
0
Order By: Relevance
“…Here, three random forest (RF) models were built to decipher the complex non-linear function relation using the ranger package in the R programming language 53 for weather normalization and source apportionment 39 , 40 . Random forest is the suitable algorithm for conducting small dataset and has been widely used in source apportionment research previously 43 , 54 . Previous research indicated that anthropogenic emissions (e.g., transport and factory emissions), biomass burning emissions, and meteorological conditions are the three crucial factors of variation of BC in the atmosphere 55 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, three random forest (RF) models were built to decipher the complex non-linear function relation using the ranger package in the R programming language 53 for weather normalization and source apportionment 39 , 40 . Random forest is the suitable algorithm for conducting small dataset and has been widely used in source apportionment research previously 43 , 54 . Previous research indicated that anthropogenic emissions (e.g., transport and factory emissions), biomass burning emissions, and meteorological conditions are the three crucial factors of variation of BC in the atmosphere 55 .…”
Section: Methodsmentioning
confidence: 99%
“…After that, an attribution technique was used to decompose the normalized BC (BC emission) concentration to traffic and public emitted BC by assuming RF algorithem well learned the relationship shown in Eq. ( 3 ) 39 , 54 . The predicted BC shows a good correlation with observed BC (Fig.…”
Section: Methodsmentioning
confidence: 99%